Effect of COVID-19 on the Wellbeing of Healthcare Professionals in Public Isolation Hospitals in Egypt - Sabbah, Shaimaa (AUC Knowledge Fountain, 2022)
One of the most vulnerable groups severely hit by the COVID-19 pandemic has been the Healthcare Professionals (HCPs), especially the physicians, pharmacists, and nurses who work in public Isolation hospitals. The Egyptian medical syndicate declared the death of more than 600 physicians from February 2020 till January 2022. In the meantime, the Egyptian government has worked on different policies for relieving the negative effects of the pandemic on this vulnerable group; however, easing restrictions, no total lockdown implementation, and monitoring bureaucracy has negatively affected the wellbeing of those HCPs. The study aims to figure out recommended policies to protect HCPs’ wellbeing during the current pandemic and help us be better prepared for future upcoming pandemics that we may face. Based on seventeen in-depth semi-structured interviews with a purposive sample of HCPs, occupying different positions and located in different geographical areas in Egypt, the study assesses the extent of the effect of the COVID-19 pandemic as a mass causality incident on HCPs perceived sense of wellbeing and its different dimensions, as defined by the Centers for Disease Control and Prevention (CDC) and relating them to different needs levels according to the Maslow’s Hierarchy of needs for recommending policies depending on their needs. Findings show that although HCPs felt a sense of pride with their work and were somehow satisfied with their financial compensation, all other dimensions of their well-being were compromised, including the physical, psychological, emotional, social, developmental, and work domain-related aspects. Physical, social, and economic wellbeing aspects were deteriorated due to the lack of basic needs. Furthermore, Emotional, psychological, development and activity, and domain specific satisfaction aspects were worsened because of depletion of the psychological needs. Accordingly, life satisfaction, and engaging activities and work aspects collapsed after the diminishing of the self-fulfillment needs. Finally, Egyptian government has learned a lesson from the COVID-19 pandemic and started to prepare for management of the future pandemic that we may face by issuing a new law (Law no. 152/2021) for combating pandemics and epidemics, which covers the first step of the disaster cycle management.